Advanced atypical lung carcinoid tumour successfully treated with carboplatin, etoposide and atezolizumab: A case report. Issue 5 (22nd April 2022) - Yamamoto, Yoshihiro; Ijichi, Kayo; Koike, Ai; Nakamura, Satoshi; Takahata, Yuriko; Okamatsu, Yuki; Fujita, Akitaka; Kawakami, Satoru; Harada, Taishi
Abstract: Atypical carcinoid tumours are relatively rare among lung cancers. Surgery is regarded as standard treatment for localized cases, but there is little established evidence on treatment strategies for advanced cases. Moreover, the efficacy of immune checkpoint inhibitors for advanced carcinoid tumours is unclear. Here, we report a case of a patient with an atypical carcinoid tumour in whom successful disease control was achieved with the use of combined cytotoxic chemotherapy and immunotherapy. Abstract : Immune checkpoint inhibitors are novel anticancer drugs increasingly used in the lung cancer field, except carcinoid tumour. We report a patient in whom an atypical carcinoid tumour was well controlled with platinum‐doublet chemotherapy and atezolizumab.